Species identification of non-hybrid and hybrid Pangasiid catfish using polymerase chain reaction-restriction fragment length polymorphism - Sriphairoj, Kednapat; Na-Nakorn, Uthairat; Klinbunga, Sirawut (Agriculture and Natural Resources, 2018)
Species-diagnostic molecular markers are essential for the identification of species groups possessing overlapping morphological characters. They also play an important role in preventing the supply of incorrect species for the food industry and in verifying the species origins of various forms of products. Molecular genetic markers were developed for the identification of six Pangasiid species-Pangasianodon gigas, Pangasianodon hypophthalmus, Pangasius bocourti, Pangasius conchophilus, Pangasius larnaudii and Pangasius sanitwongsei-based on restriction analysis of mitochondrial 16S ribosomal (r) DNA with Tsp 509I, Hinc II and Mfe I and nuclear immunoglobulin M heavy chain constant region (IgM-H) with Taq I and Pst I. Six non-overlapping composite restriction fragment length polymorphism (RFLP) patterns: AAB (AA) (AA), ACB(AA) (BB), BBB(BB) (BB), CCB(BB) (BB), DCA (BB) (CC) and DCB(-) (-) were observed across the respective species. Larvae of P. gigas, P. hypophthalmus, P. bocourti, P. larnaudii and P. sanitwongsei could be unambiguously differentiated using polymerase chain reaction (PCR)-RFLP analysis of 16S rDNA. In addition, detection of P. hypophthalmus x P. gigas, P. hypophthalmus x P. bocourti and P. hypophthalmus x P. larnaudii hybrids could be carried out using PCR-RFLP analysis of IgM-H.